Analysis of the Implementation of Arabic Language Environment (Bi’ah Lughawiyah) to Improve Speaking Proficiency at Ma’had Bina Madani: English - efendi, Agung; muttaqien, Agung; Siti Khumairotuzzahra (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2025)
Arabic is important to master, especially in pesantren such as Ma'had Bina Madani, particularly in Islamic boarding schools such as Ma'had Bina Madani. This study aims to analyze the implementation of bi'ah lughawiyah at Ma'had Bina Madani in enhancing the Arabic speaking skills of students. The method employed in this research is a qualitative descriptive approach through observation, interviews, and document collection. The findings of this study indicate that the implementation of bi'ah lughawiyah at Ma'had Bina Madani has successfully established a planned, consistent, and applicable Arabic language teaching environment. Daily, weekly, and monthly activities involving teachers, OSIS administrators, and foreign sheikhs as language models also support this success. The combination of theory and practice is the primary factor determining the success of bi'ah lughawiyah implementation. This study confirms that a coordinated and consistent language environment can improve students' Arabic speaking skills. The implementation of bi'ah lughawiyah has a positive impact on increasing students' confidence, fluency, understanding of language structure, and motivation to communicate in Arabic. This research contributes to the development of efficient and practical Arabic language teaching methods in Islamic boarding schools. Therefore, this study can serve as a reference for Islamic educational institutions in supporting the improvement of Arabic language skills among students.